Nurtured : postpartum care : an exegesis presented in partial fulfilment of the requirements for a Master of Design at Massey University, Wellington, New Zealand. EMBARGOED until 12th March 2028 - Nicholls, Isabel (Massey University, 2025)
A range of challenges accompanies childbirth. Physical pain, discomfort, emotional uncertainty, and significant life changes are inevitable among these. A number of products exist to meet the varying needs of postpartum care. Few, however, fully address the broad spectrum of challenges faced by women during this vulnerable period. Prioritising comfort and support while addressing individual needs will ultimately enhance the postpartum experience for new mothers. This research focused on the design of innovative, empathetic, versatile, and safe underwear in the immediate postpartum period when lochia (postpartum discharge) and pain are experienced. Participants in semi-structured qualitative interviews and quantitative surveys emphasised the need for comfort, breathability, and absorbency, as well as suitability for a range of postpartum injuries and the accommodation of physiological changes in the body. This action-based research included iterative design processes alongside functional and user testing. While developing effective and satisfying products for new mothers, it is important to also explore the crossover of sustainable design strategies within women’s health. Postpartum products are not intended for long-term use, with their usage depending both on the number of pregnancies and the speed of postpartum recovery. While postpartum and pregnancy care are my target market, there are also secondary uses for this product including menstruation, incontinence, miscarriage, or surgical procedures which result in vaginal or uterine bleeding. This aspect of the research was supported through surveys and interviews of both professionals and users, whose feedback was critical to the design process. The underwear designed through this research uses a combination of novel features associated with reusable period underwear paired with postpartum underwear and includes heating and cooling for pain relief. The key pillars of research and innovation include digital knitting teamed with material exploration and engineered stretch and compression. This work has culminated in postpartum underwear that is reusable, comfortable, absorbent, and promotes healing after birth.
Embargoed until 12th March 2028
Keywords: Industrial design; textile design; fashion design; women’s health; postpartum care; comfort; absorbent; versatile; material properties; advancing technology; knitting; 330309 Industrial and product design